Reactive power optimization in distribution systems considering load levels for economic benefit maximization - Srinivasan, G.; Mahesh Kumar Reddy, V.; Venkatesh, P.; Parimalasundar, E. (Electrical Engineering & Electromechanics, 2023)
Introduction. The need for electrical energy has been increased sharply due to hasty growth in industrials, social and economic improvements. From the previous studies, it has been agreed that almost 13 % of the total power generated is wasted as heat loss at distribution level. It has been extensively recognized that the node voltage profile along the distribution system can be enhanced under steady state power transfer controlled by proper reactive power compensation. Capacitors have been acknowledged as reactive power compensating device in distribution systems to achieve technical and economical benefits. Novelty of this work is the application of Archimedes optimization algorithm for reactive power optimization in distribution systems so as to obtain an improved solution and also a real 94-bus Portuguese network and modified 12-bus network has been taken and validated for three different load levels which are totally new. Purpose of the proposed work is to maximize the economic benefit by reducing the power loss and capacitor purchase cost at three different load conditions subject to satisfaction of equality and inequality constraints. Methods. The economic benefit has been validated using Archimedes optimization algorithm for three load levels considering three distribution systems. Results. The computational outcomes indicated the competence of the proposed methodology in comparison with the previously published works in power loss minimization, bus voltage enhancement and more economical benefit and proved that the proposed methodology performs well compared to other methods in the literature.